Frontiers in blockchain - Frontiers Research Foundation (Frontiers Media S.A, 2018)
"Frontiers in Blockchain publishes rigorously peer-reviewed research covering all theory and applications of blockchain and blockchain-related technologies"--Publisher.
Keywords: Blockchains (Databases) : Periodicals; Blockchains (Databases)